Transparent nepheline glass ceramic, chemically strengthened glass ceramic and preparation method and application thereof

By adjusting the primary and secondary crystal phase composition and process parameters of transparent xiashi microcrystalline glass and chemically strengthened microcrystalline glass, the problem of insufficient performance of existing microcrystalline glass is solved, and high-performance and low-cost microcrystalline glass preparation is achieved, suitable for electronic products and vehicle-mounted display equipment.

CN119874200APending Publication Date: 2025-04-25深圳市昊迦科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510093741.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The optical and mechanical properties of existing microcrystalline glass are not sufficient to meet the needs of consumer electronic products and vehicle display equipment, and the traditional microcrystalline glass preparation process consumes a lot of energy and time.

Method used

Transparent cherry crystal glass and chemically strengthened microcrystalline glass are used to adjust the composition and proportion of the main and secondary crystal phases, optimize the grain size and crystallinity, and adopt a primary heat treatment process to reduce energy consumption.

Benefits of technology

It improves the average transmittance and mechanical properties of microcrystalline glass, reduces preparation costs and energy consumption, and is suitable for screen protection cover materials for consumer electronic products and on-board display equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874200A_ABST
    Figure CN119874200A_ABST
Patent Text Reader

Abstract

The invention discloses a transparent nepheline glass ceramic, a chemical reinforced glass ceramic and a preparation method and application of the transparent nepheline glass ceramic, the chemical reinforced glass ceramic and the preparation method and application of the chemical reinforced glass ceramic. A principal crystalline phase is sodium nepheline, triclinic nepheline and aluminum phosphate, and a secondary crystalline phase is at least one of sodium silicate, beta quartz solid solution and zirconium oxide; the main crystal phase meets the following conditions: the mass ratio of the netsonite crystal form is X, the average grain size is R1nm, and R1 is more than or equal to 35nm and less than or equal to 65nm; the mass ratio of the cabernet crystal form is Y, the average grain size is R2nm, and R2 is greater than or equal to 25nm and less than or equal to 50nm; the mass ratio of the aluminum phosphate crystal form is Z, the average grain size is R3 nm, and R3 is larger than or equal to 15 nm and smaller than or equal to 35 nm; x, Y and Z satisfy 70: 20: 10 < = X: Y: Z < = 85: 10: 5; the total mass ratio of all sub-crystalline phases in the transparent nepheline microcrystalline glass is L, and L is more than 0% and less than or equal to 5%. The microcrystalline glass provided by the invention has excellent optical properties and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass-ceramics, and in particular to transparent nepheline glass-ceramics, chemically strengthened glass-ceramics, and preparation methods and applications thereof. Background Art

[0002] Glass materials are used in screen protection of consumer electronic products (such as watches, tablets, mobile phones, notebooks and cameras, etc.) and vehicle-mounted display devices. While meeting the excellent optical properties of high transmittance and low haze, they also need to have excellent mechanical properties to reduce the breakage rate of the equipment during use and extend its service life.

[0003] The main crystal forms of currently popular transparent microcrystalline glass are the LAS system with lithium (Li) as the main element and the MAS spinel system with magnesium-aluminum-zinc (Mg-Al-Zn) as the main element. The LAS system requires a large amount of lithium-containing compounds, and lithium is an important component of new energy storage materials. The cost of lithium-containing compounds is high, such as lithium carbonate. In the MAS spinel system, the optical properties of the crystal phase in the microcrystalline glass are quite different from the optical properties of the remaining glass phase. In order to ensure the excellent optical properties and mechanical properties suitable for cover glass materials, the crystal parameters of the MAS spinel system are difficult to control and the manufacturing process is complicated.

[0004] At the same time, in the process of microcrystallization heat treatment of basic glass, at least two-stage heat treatment of "nucleation-crystallization" is usually adopted, which consumes a lot of energy and time costs.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides transparent nepheline glass-ceramics, chemically strengthened glass-ceramics, and preparation methods and applications thereof, so as to solve the problem that the optical and mechanical properties of existing glass-ceramics are not sufficient to meet the demand.

[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0008] In a first aspect of the present invention, a transparent nepheline glass-ceramics is provided, wherein the main crystal phase of the transparent nepheline glass-ceramics is sodium nepheline, triclinic nepheline and aluminum phosphate, and the secondary crystal phase is at least one of sodium silicate, β-quartz solid solution and zirconium oxide;

[0009] The main crystalline phase meets the following characteristics:

[0010] A) The mass percentage of sodium nepheline crystal is X, and the average grain size is R 1 nm, 35nm≤R 1 ≤65nm;

[0011] B) The mass percentage of triclinic nepheline crystal is Y, and the average grain size is R 2 nm, 25nm≤

[0012] R 2 ≤50nm;

[0013] C) The mass proportion of aluminum phosphate crystal is Z, and the average grain size is R 3 nm, 15nm≤R 3 ≤35nm;

[0014] The relationship between X, Y, and Z satisfies 70:20:10≤X:Y:Z≤85:10:5;

[0015] The total mass percentage of all secondary crystalline phases in the transparent nepheline glass-ceramics is L, 0%<L≤5%;

[0016] The average grain size of the transparent nepheline glass-ceramics is 20-60nm;

[0017] The transparent nepheline glass-ceramics has a crystallinity of 20%-70%.

[0018] Preferably, in terms of molar percentage, the composition of the transparent nepheline glass-ceramics includes: 42.0-53.0% SiO 2 , 16.5-21.0% Al 2 O 3 , 17.5-22.5% Na 2 O, 0-1.0% K 2 O, 4.0-9.0% Li 2 O, 2.0-5.0% B 2 O 3 , 1.2-4.5% ZrO 2 , 0-0.5% TiO 2 , 1.0-3.5% P 2 O 5 , 0-2.0% MgO, 0.1-0.5% SnO 2 ;

[0019] The molar numbers of the components of the transparent nepheline glass-ceramics satisfy at least one of the following relationships:

[0020] 1)0.6≤(Al 2 O 3 / Na 2 O)≤1.2;

[0021] 2) 23.0%≤(Na 2 O+Li 2 O+K2 O)%≤30.50%;

[0022] 3) 2.0%≤(ZrO 2 +P 2 O 5 )%≤7.0%;

[0023] 4)2.25≤(SiO 2 +Al 2 O 3 ) / (Na 2 O+Li 2 O+K 2 O)≤2.75.

[0024] Preferably, the transparent nepheline glass-ceramics further comprises rare earth element oxides, wherein the molar ratio of the rare earth element oxides in the transparent nepheline glass-ceramics is at least 0.10%, and the rare earth element oxides are Y 2 O 3 ,La 2 O 3 One of them.

[0025] Preferably, the transparent nepheline glass-ceramics further comprises a clarifier, and in the transparent nepheline glass-ceramics, the molar ratio of the clarifier is 0.1-0.50%, and the clarifier is NaCl, Sb 2 O 3 、As 2 O 3 , nitrate, and sulfate.

[0026] Preferably, the transparent nepheline glass-ceramics has an elastic modulus ≥75 Gpa, a shear modulus ≥34 Gpa, and a Poisson's ratio between 0.15 and 0.20.

[0027] The second aspect of the present application provides a method for preparing the above-mentioned transparent nepheline glass-ceramics, the preparation method comprising the following steps:

[0028] The compounds corresponding to the above oxides are mixed, melted, clarified, formed, and annealed to obtain a basic glass;

[0029] The base glass is heated to 590°C-680°C at a heating rate of 1-15°C / min, and kept warm for 15-120 minutes to obtain the transparent nepheline glass-ceramics.

[0030] In a third aspect of the present application, a method for preparing a chemically strengthened glass-ceramic is provided, the method comprising the following steps:

[0031] The transparent nepheline glass-ceramics prepared above was placed in a molten state of LiNO at a temperature of 420°C-480°C.3 、NaNO 3 、KNO 3 Or at least two of the three are immersed in a mixed molten salt for 2-10 hours to obtain the chemically strengthened microcrystalline glass.

[0032] In a fourth aspect of the present application, a chemically strengthened glass-ceramics is provided, wherein the chemically strengthened glass-ceramics is prepared by the above-mentioned preparation method.

[0033] Preferably, when the thickness of the chemically strengthened glass-ceramics is less than 0.70 mm, for light in the wavelength range of 400 nm-780 nm, the transmittance Tr of the chemically strengthened glass-ceramics is ≥ 88%, the color control LAB value is 0.80≤|B|≤1.40, and Haze≤0.20%;

[0034] The surface four-point bending strength of the chemically strengthened glass-ceramics is ≥600Mpa, and the extrusion strength is ≥15Kgf;

[0035] Under the impact of 80-grit sandpaper and a 200g weight, the chemically strengthened microcrystalline glass can withstand a height of ≥150cm and an impact energy of ≥0.30 joules.

[0036] The fifth aspect of the present application provides the application of the above-mentioned transparent nepheline glass-ceramics or the above-mentioned chemically strengthened glass-ceramics in screen protection cover materials for consumer electronic products and vehicle-mounted display devices.

[0037] Beneficial effects:

[0038] The present invention discloses transparent nepheline glass-ceramics, chemically strengthened glass-ceramics, and preparation methods and applications thereof. The main crystal forms in the transparent nepheline glass-ceramics and chemically strengthened glass-ceramics provided by the present invention include sodium nepheline, triclinic nepheline and aluminum phosphate. The grain sizes of the three main crystal forms are within a certain range, and the proportions of the three main crystal forms satisfy a certain relationship. In addition, the proportions of the main and secondary crystal forms in the transparent nepheline glass-ceramics and chemically strengthened glass-ceramics provided by the present invention are within a specific range, which can fully ensure the refractive index difference between the crystal phase and the glass phase in the transparent nepheline glass-ceramics and the chemically strengthened glass-ceramics, thereby improving the average transmittance of the transparent nepheline glass-ceramics and the chemically strengthened glass-ceramics.

[0039] The transparent nepheline glass-ceramics and chemically strengthened glass-ceramics provided by the present invention belong to Na 2 O-Al 2 O 3 -SiO 2(NAS) system uses Na as one of the main elements of the crystal phase and has excellent mechanical and optical properties. The Li element used in the present invention only exists in the glass phase of the transparent nepheline glass-ceramics and chemically strengthened glass-ceramics of the present invention, and its function is to reduce the melting difficulty of the base glass and participate in chemically strengthened ion exchange. It is completely different from the LAS system glass-ceramics with Li as the main element of the crystal phase on the current market, and greatly reduces the use of lithium carbonate.

[0040] At the same time, in the present invention, microcrystalline glass can be formed by subjecting the base glass to heat treatment only once. This is different from the traditional microcrystalline glass which requires at least two stages of "nucleation-crystallization" heat treatment to complete the microcrystallization process. This can greatly save energy and time costs, reduce the cost of use, and greatly improve the application of microcrystalline glass.

[0041] The transparent nepheline glass-ceramics and chemically strengthened glass-ceramics provided by the present invention have excellent optical properties and mechanical properties, and can be applied to the display screen cover material market of consumer electronic products and vehicle-mounted display devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 XRD spectrum of the transparent nepheline glass-ceramics prepared in Example 1 of the present invention;

[0043] Figure 2 The Na of the transparent nepheline glass-ceramics prepared in the preferred embodiment of the present invention is 2 O-Al 2 O 3 -SiO 2 Phase diagram;

[0044] Figure 3 It is the average transmittance of the transparent nepheline glass-ceramics prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The present invention provides transparent nepheline glass-ceramics, chemically strengthened glass-ceramics, and preparation methods and applications thereof. To make the purpose, technical scheme, and effects of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0046] In order to better understand the content of the present invention, some terms in the present invention are explained:

[0047] Basic glass: Glass that has not been nucleated, crystallized or chemically strengthened by ion exchange is made by uniformly mixing compounds containing various oxides (including silicon dioxide, aluminum oxide, sodium oxide, calcium oxide, etc.), melting them at high temperature, and then forming them by one of the following methods: float method, overflow down-draw method, roller pressing method or casting method.

[0048] Glass-ceramics: A type of solid composite material that contains both a glass phase and a crystal phase (microcrystalline phase, crystalline phase) and is prepared by subjecting base glass to a targeted controlled crystallization treatment.

[0049] Nucleation: The base glass is heat treated to make the nucleating material in the glass grow tiny crystal nuclei.

[0050] Crystallization: The base glass is grown into a certain crystal based on the crystal nucleus through heat treatment.

[0051] Crystalline phase: It is the microscopic structure of crystals and is a general term for parts composed of a large number of crystalline solid phases.

[0052] Crystallinity: It is used to indicate the proportion of the crystallized area in (chemically strengthened) microcrystalline glass, generally based on the volume ratio of the crystal phase in the entire microcrystalline glass.

[0053] Elastic modulus: refers to the proportional constant between the longitudinal stress and the longitudinal strain acting on the material within the range of elastic deformation (i.e. within the proportional limit).

[0054] Shear modulus: refers to the ratio of shear stress to shear strain.

[0055] Poisson's ratio: The absolute value of the ratio of the lateral strain caused by a uniformly distributed longitudinal stress to the corresponding longitudinal strain within the proportional limit of the material.

[0056] The embodiment of the present invention provides a transparent nepheline glass-ceramics, wherein the main crystal phase of the transparent nepheline glass-ceramics is sodium nepheline, triclinic nepheline and aluminum phosphate, and the secondary crystal phase is at least one of sodium silicate, β-quartz solid solution and zirconium oxide;

[0057] The main crystalline phase meets the following characteristics:

[0058] A) The mass percentage of sodium nepheline crystal is X, and the average grain size is R 1 nm, 35nm≤R 1 ≤65nm;

[0059] B) The mass percentage of triclinic nepheline crystal is Y, and the average grain size is R 2 nm, 25nm≤

[0060] R 2 ≤50nm;

[0061] C) The mass proportion of aluminum phosphate crystal is Z, and the average grain size is R 3 nm, 15nm≤R 3 ≤35nm;

[0062] The relationship between X, Y, and Z satisfies 70:20:10≤X:Y:Z≤85:10:5;

[0063] The total mass percentage of all secondary crystalline phases in the transparent nepheline glass-ceramics is L, 0%<L≤5%;

[0064] The average grain size of the transparent nepheline glass-ceramics is 20-60nm, preferably 20-50nm;

[0065] The crystallinity of the transparent nepheline glass-ceramics is 20%-70%, preferably 20%-65%.

[0066] The main crystal forms in the transparent nepheline glass-ceramics and chemically strengthened glass-ceramics provided by the embodiments of the present invention include sodium nepheline, triclinic nepheline and aluminum phosphate. The grain sizes of the three main crystal forms are within a certain range, and the proportions of the three main crystal forms satisfy a certain relationship. In addition, the proportions of the main and secondary crystal forms in the transparent nepheline glass-ceramics and chemically strengthened glass-ceramics provided by the present invention are within a specific range, which can fully ensure the refractive index difference between the crystal phase and the glass phase in the transparent nepheline glass-ceramics and the chemically strengthened glass-ceramics, thereby improving the average transmittance of the transparent nepheline glass-ceramics and the chemically strengthened glass-ceramics.

[0067] In some embodiments, the transparent nepheline glass-ceramics comprises, by mole percentage, 42.0-53.0% SiO 2 , 16.5-21.0% Al 2 O 3 , 17.5-22.5% Na 2 O, 0-1.0% K 2 O, 4.0-9.0% Li 2 O, 2.0-5.0% B 2 O 3 , 1.2-4.5% ZrO 2 , 0-0.5% TiO 2 , 1.0-3.5% P 2 O 5 , 0-2.0% MgO, 0.1-0.5% SnO 2 ;

[0068] The molar numbers of the components of the transparent nepheline glass-ceramics satisfy at least one of the following relationships:

[0069] 1)0.6≤(Al 2 O 3 / Na 2 O)≤1.2;

[0070] 2) 23.0% ≤ (Na 2 O+Li2 O+K 2 O)%≤30.50%;

[0071] 3) 2.0%≤(ZrO 2 +P 2 O 5 )%≤7.0%;

[0072] 4)2.25≤(SiO 2 +Al 2 O 3 ) / (Na 2 O+Li 2 O+K 2 O)≤2.75.

[0073] SiO 2 As one of the main components of the network oxide of basic glass and microcrystalline glass, it is one of the important components that constitute the Si-O tetrahedron in the main body and form the network structure. 2 The molar percentage of SiO is 42.0-53.0%, preferably 45-53%, for example, it can be 42.0%, 43.0%, 44.0%, 45.0%, 46.0%, 47.0%, 48.0%, 49.0%, 50.0%, 51.0%, 52% and 53% and any one of the components in the range of any two of the above values. 2 When the content is too low (less than 42.0%), the products made of the material have poor resistance to devitrification, poor scratch resistance and low hardness. 2 When the content is greater than 53.0%, it is difficult to control the composition and size of the precipitated crystals after heat treatment;

[0074] Al 2 O 3 and Na 2 O is the main component of the crystal forms of sodium nepheline, triclinic nepheline, sodium silicate, β-quartz solid solution, etc. in the embodiment of the present invention. The proportion of the two components must meet certain conditions to form a microcrystalline glass in which the proportion of triclinic nepheline in the main crystal form exceeds that of sodium nepheline. Specifically, Al 2 O 3 As one of the main components of the internal network structure of base glass and microcrystalline glass, and also the main component of sodium nepheline, triclinic nepheline and other crystal forms, it can significantly improve the thermal stability and ion exchange performance, and help to generate the target crystal. Based on the materials involved in the embodiments of the present invention, Al 2 O 3The molar percentage of Al is 16.50-21.0%, preferably 17.50-21.0%, for example, 16.50%, 17.0%, 18.0%, 19.0%, 20.0%, 21.0% and any two of the above values ​​can be selected. 2 O 3 When the molar content exceeds 21.0%, it is easy to cause the transmittance to decrease, the high-temperature viscosity to increase, and the melting point to increase, which is not conducive to production. 2 O is sodium nepheline (NaAlSiO 4 ), triclinic nepheline (Na 7.85 Al 7.85 Si 8.15 O 32 ) and is also an important element for ion exchange in the chemical strengthening process of glass-ceramics. 2 O is a flux when the base glass is melted at high temperature, which can significantly reduce the melting temperature of the base glass. 2 The molar percentage range of O is 17.50-22.5%, preferably 18.0-22.0%, specifically 17.50%, 18.0%, 19.0%, 20.0%, 21.0%, 22.0%, 22.50% and any value in any two of the above composition ranges.

[0075] At the same time 2 O.K 2 O and Li 2 The three alkali metal oxides can effectively reduce the viscosity of the basic glass when the basic glass is melted, especially in the embodiment of the present invention, Al 2 O 3 The content is much higher than that in LAS system microcrystalline glass. Moreover, the proportion of the three alkali metal element oxides also needs to meet certain conditions to ensure the content relationship between the main and secondary crystal forms in the present invention, among the three alkali metals.

[0076] K 2 O is often added to reduce the high temperature viscosity of the base glass, significantly improve the formability and fluidity of the base glass at high temperature, and significantly reduce the incidence of cracks. 2 O, can slow down the crystallization behavior of the base glass during molding. The materials involved in the embodiments of the present invention, K 2The molar content range of O is 0.0-1.0%, preferably 0.0-0.50%. In the present invention, it can be 0.0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% and any value in the range consisting of any two of the above values.

[0077] Li 2 O is an oxide with high alkali metal activity and is an external oxide of the base glass network. As one of the additives to reduce the high temperature viscosity of the base glass, it can significantly improve the high temperature fluidity of the base glass. + In the transparent nepheline glass-ceramics provided by the present invention, ion exchange chemical strengthening reaction can be involved to further enhance the mechanical properties of the transparent nepheline glass-ceramics. The transparent nepheline glass-ceramics involved in the present invention, Li 2 The molar content of O is in the range of 4.0-9.0%, preferably 4.50-9.0%. In the present invention, it can be 4.0%, 4.5%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0% and any value in the range consisting of any two of the above values.

[0078] B 2 O 3 and MgO as the outer oxide of the glass network, which can effectively ensure the chemical stability of the base glass and microcrystalline glass. 2 O 3 The linear thermal expansion coefficients of the base glass and the glass-ceramics can be controlled, while maintaining the chemical durability and mechanical strength of the ceramicized main body glass-ceramics. 2 O 3 The molar content range is 2.0-5.0%, preferably 2.5-5.0%, and in the present invention, it can be 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0% and any value in the range of any two of the above values. 2 O 3 The content makes the chemical resistance of the microcrystalline glass material formed after the basic glass nucleation and crystallization unstable.

[0079] MgO, as a divalent alkaline earth metal, can effectively break the bridging oxygen bond of Si-O tetrahedron inside the base glass. 2+ It is beneficial to promote the glass to have a lower refractive index and density in the tetrahedron. In the embodiment of the present invention, the molar content of MgO is in the range of 0-2.0%, specifically 0%, 0.50%, 1.50%, 2.0% and any value in the range consisting of any two of the above values.

[0080] ZrO 2 、TiO 2 and P 2 O 5 The three oxides are usually used as important nucleating agents in glass-ceramics, especially ZrO 2 and P 2 O 5 The proportion of the total components can significantly affect the growth of crystals in microcrystalline glass, and also affect the optical properties of microcrystalline glass. However, due to the different effects of the three components, there are significant differences: ZrO 2 In the base glass and transparent nepheline glass-ceramics of the present invention, ZrO 2 The stability of the glass can be improved by significantly reducing the devitrification of the glass during the formation process and lowering the liquidus temperature. At high temperatures, a small amount of zirconium dioxide reacts with silicon dioxide to form ZrSiO 4 , ZrSiO 4 A main liquidus phase can be formed, which significantly reduces the liquidus viscosity. 2 The tetragonal modification can increase the strength and toughness of the glass-ceramics; in the embodiment of the present invention, ZrO 2 The molar content range is 1.2-4.5%, specifically 1.2%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5% and any value in the range consisting of any two of the above values.

[0081] P 2 O 5 It can be used as a nucleating agent in base glass and glass-ceramics to form bulk nucleation, which can promote the phase separation and overall crystallization ability of base glass, and can also form sodium phosphate crystals. 2 O 5 If the concentration is too low, the base glass will not be easy to crystallize during heat treatment, and crystals will only form from the surface to the inside at a higher temperature and lower viscosity. 2 O 5 If the concentration is too high, it will be difficult to control the devitrification when cooling during the formation of the base glass; 2 O 5 The molar content range is 1.0-3.5%, specifically 1.0%, 1.50%, 2.0%, 2.5%, 3.0%, 3.5% and any value in the range consisting of any two of the above values.

[0082] TiO 2 In the base glass and glass-ceramics of the embodiments of the present invention, TiO 2 Ti 4+The body-centered octahedral structural unit, and 6 O 2- Coordinated in six directions, containing 1 Ti 4+ The oxygen octahedron can effectively promote the growth of the crystal nucleus of the base glass during the nucleation and crystallization heat treatment process, and at the same time improve the stability of the glass; TiO 2 The introduction of TiO 2 The introduction of TiO can easily cause phase separation in the base glass, leading to crystallization and affecting the formation of glass. 2 At the same time, it will also cause the base glass to darken in color, affecting the optical properties of the microcrystalline glass. 2 The molar content range is 0-0.50%, specifically 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% and any value in the range consisting of any two of the above values.

[0083] SnO 2 It is an effective clarifier for basic glass. Its introduction is beneficial to reducing the formation of gas defects in the glass melt, reducing the number of melt bubbles, and improving the clarification effect. In the embodiment of the present invention, SnO 2 The content range is 0.1-0.5%, specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5% and any value in the range consisting of any two of the above values.

[0084] In some embodiments, the transparent nepheline glass-ceramics further comprises rare earth element oxides, wherein the molar ratio of the rare earth element oxides in the transparent nepheline glass-ceramics is at least 0.10%, and the rare earth element oxides are Y 2 O 3 ,La 2 O 3 One of them.

[0085] In some embodiments, the transparent nepheline glass-ceramics further comprises a clarifier, wherein the molar ratio of the clarifier in the transparent nepheline glass-ceramics is 0.1-0.50%, and the clarifier is NaCl, Sb 2 O 3 、As 2 O 3 , nitrate, and sulfate.

[0086] The clarifier can homogenize the oxides of the base glass in a molten state and evenly distribute the oxides in the glass body. The molar content of the clarifier in the embodiment of the present invention is in the range of 0.1-0.50%, specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5% and any value in the range formed by any two of the above values.

[0087] In some embodiments, the transparent nepheline glass-ceramics has an elastic modulus of ≥75 Gpa, a shear modulus of ≥34 Gpa, and a Poisson's ratio between 0.15 and 0.20.

[0088] The embodiment of the present invention provides a method for preparing the above-mentioned transparent nepheline glass-ceramics, and the preparation method comprises the following steps:

[0089] The compounds corresponding to the above oxides are mixed, melted, clarified, formed, and annealed to obtain a basic glass;

[0090] The base glass is heated to 590°C-680°C at a heating rate of 1-15°C / min, and kept warm for 15-120 minutes to obtain the transparent nepheline glass-ceramics.

[0091] An embodiment of the present invention provides a method for preparing chemically strengthened glass-ceramics, the method comprising the following steps:

[0092] The transparent nepheline glass-ceramics prepared above was placed in a molten state of LiNO at a temperature of 420°C-480°C. 3 、NaNO 3 、KNO 3 Or at least two of the three are immersed in a mixed molten salt for 2-10 hours to obtain the chemically strengthened microcrystalline glass.

[0093] An embodiment of the present invention provides a chemically strengthened glass-ceramics, and the chemically strengthened glass-ceramics is prepared by the above-mentioned preparation method.

[0094] In some embodiments, when the thickness of the chemically strengthened glass-ceramics is less than 0.70 mm, for light in the wavelength range of 400 nm-780 nm, the transmittance Tr of the chemically strengthened glass-ceramics is ≥ 88%, the color control LAB value is 0.80≤|B|≤1.40, and Haze≤0.20%;

[0095] The surface four-point bending strength of the chemically strengthened glass-ceramics is ≥600Mpa, and the extrusion strength is ≥15Kgf;

[0096] Under the impact of 80-grit sandpaper and a 200g weight, the chemically strengthened microcrystalline glass can withstand a height of ≥150cm and an impact energy of ≥0.30 joules.

[0097] The embodiments of the present invention provide the application of the above-mentioned transparent nepheline glass-ceramics or the above-mentioned chemically strengthened glass-ceramics in screen protection cover materials for consumer electronic products and vehicle-mounted display devices.

[0098] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are only for illustrating the present invention but not limiting the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0099] Example 1

[0100] A preparation method of chemically strengthened glass-ceramics comprises the following steps:

[0101] The basic glass is prepared by a casting method: the compounds corresponding to the above oxide components are mixed evenly, melted at 1550-1600°C for 3-5 hours, stirred during the melting process, and then cast in a mold composed of steel bars and steel blocks at a high temperature of 1400°C in a molten state to form a rectangular glass brick, and annealed to obtain a block-shaped basic glass brick;

[0102] Preparation of transparent nepheline glass-ceramics: The basic glass bricks obtained above are placed in a precision crystallization furnace (or tunnel kiln) for a heat treatment to obtain transparent nepheline glass-ceramics.

[0103] Preparation of chemically strengthened glass-ceramics: The transparent nepheline glass-ceramics obtained above were shaped, cut, and polished to obtain glass-ceramics sheets of 50 mm*50 mm*0.65 mm in size, which were then immersed in KNO 3 、NaNO 3 Chemical strengthening is carried out in a mixed molten salt to obtain chemically strengthened microcrystalline glass.

[0104] Embodiment 2-7

[0105] Examples 2-7 adopt a preparation method that is substantially the same as that of Example 1, except that the components of the prepared base glass are different, the temperature and time of nucleation and crystallization are different, and the processing parameters of chemical strengthening are different.

[0106] The compositions of the basic glasses prepared in Examples 1-7 are shown in Table 1, the temperature and time operation parameters of nucleation and crystallization are shown in Table 2, and the specific chemical strengthening treatment parameters are shown in Table 3.

[0107] Table 1

[0108]

[0109]

[0110] Table 2

[0111]

[0112] Testing equipment and testing method for transparent nepheline glass-ceramics after crystallization of base glass: XRD test: Grind the glass-ceramics sheet into fine glass powder with a grinder, and test it with Rigaku Smartlab X-ray diffraction (XRD) under the conditions of diffraction angle range 2θ of 10°~80°, scanning speed of 10° / min, working voltage of 40kV, and working current of 30mA to obtain XRD diffraction peak curve, such as Figure 1 shown.

[0113] The professional processing software Jade is used to analyze the XRD diffraction data, analyze the type, size and proportion of the crystal phase contained in the transparent glass-ceramics, and fit the diffraction peak curve to obtain the total content of the crystal phase in the transparent glass-ceramics.

[0114] Table 3

[0115]

[0116]

[0117] The chemically strengthened glass-ceramics were tested for various optical and mechanical indicators in the following manner (at least 10 samples of the above-mentioned size specifications were tested and the average value was taken in the present invention):

[0118] Transmittance test: Use PerkinElmer Lambda UV-visible spectrophotometer, refer to GB / T40415 standard, and test its average transmittance (i.e. visible light transmittance) in the wavelength range of 380nm-800nm;

[0119] Haze test: The test was conducted using a Konica Minolta spectrophotometer CM-3600A. The light receiving optical system was transmission, the spectroscopic method was a diffraction grating, the wavelength range was 360-960nm, the wavelength spacing was 10nm, the illumination source was a pulsed xenon lamp X4, the ambient temperature of the instrument was 24°C, and the air humidity was 40%.

[0120] Color control LAB value B value test: LAB is a color model based on physiological characteristics, where L represents brightness, A includes colors from dark green to gray to bright pink, and B includes colors from bright blue to gray to yellow. The B value in LAB can represent the deviation between yellow and blue of an object. Tested by Konica Minolta Spectrophotometer CM-3600A.

[0121] Four-point bending test: A microcomputer-controlled electronic universal testing machine is used, with sample specifications of 50mm*50mm*0.7mm or less in thickness, and the reinforced glass ceramics are tested in accordance with ASTMC158-2002 standard.

[0122] Extrusion performance test: Place the reinforced glass ceramic on the bottom ring of the tensile testing machine (LT-850A), start the test software, and set the moving speed of the extrusion rod (rod diameter 8mm, indenter arc radius 10mm) to 50mm / min. Click to start the test. The extrusion rod will apply force to the center of the reinforced glass ceramic piece to be tested at the set moving speed until the reinforced glass ceramic cracks and breaks. The test software will automatically read the force (N) when the reinforced glass ceramic breaks as the test result. Take 10 reinforced glass ceramic samples in the same state for testing and take the average value of the test results.

[0123] Impact resistance overall drop test: Among multiple identical reinforced glass-ceramic samples, the ratio of the sum of the measured sandpaper drop heights of each sample and the number of reinforced glass-ceramic samples is used to characterize the drop resistance of the reinforced glass-ceramic.

[0124] The specific test process is: take at least 10 pieces of the same reinforced glass ceramic samples for testing each time to obtain the average sandpaper drop resistance height. Among them, the test method for the sandpaper drop resistance height of each reinforced glass ceramic sample is:

[0125] (1) Stick 80-grit sandpaper on the lower surface of a 200g model machine and place the model machine on a green LT-SKDL-CD drop machine.

[0126] (2) Place a 50mm*50mm*0.7mm long, wide and thick reinforced glass-ceramic sample to be tested directly under the model machine, with the reinforced glass-ceramic sample facing the sandpaper, and drop the model machine at a certain drop height to impact the reinforced glass-ceramic sample directly under the model machine. If the reinforced glass-ceramic sample does not break, the drop height of the model machine is increased according to a certain rule. For example, the drop height starts from 40cm, and the reinforced glass-ceramic sample is dropped once. If it does not break, increase the height by 10cm each time and drop again until the reinforced glass-ceramic sample breaks.

[0127] (3) The last drop height of the strengthened glass-ceramic sample when it is broken is recorded as the anti-sandpaper drop height. For example, if the drop height when it is broken is 100 cm, then the anti-sandpaper drop height of the sample is 90 cm.

[0128] Young's Modulus, Shear Modulus and Poisson's Ratio Testing: Young's modulus, shear modulus and Poisson's ratio are all measured at the same time using resonant ultrasonic spectroscopy.

[0129] The performance of the heat-treated and chemically strengthened glass-ceramics prepared in Examples 1-7 was tested, and the performance indicators are shown in Table 4:

[0130] Table 4

[0131]

[0132]

[0133] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A transparent nepheline glass-ceramic, characterized in that: The main crystal phase of the transparent nepheline glass-ceramics is sodium nepheline, triclinic nepheline and aluminum phosphate, and the secondary crystal phase is at least one of sodium silicate, β-quartz solid solution and zirconium oxide; The main crystalline phase meets the following characteristics: A) The mass percentage of sodium nepheline crystal is X, and the average grain size is R1 nm, 35nm≤R1≤65nm; B) The mass proportion of triclinic nepheline crystal is Y, and the average grain size is R2 nm, 25nm≤ R2≤50nm; C) The mass proportion of aluminum phosphate crystal is Z, and the average grain size is R3 nm, 15nm≤R3≤35nm; The relationship between X, Y, and Z satisfies 70:20:10≤X:Y:Z≤85:10:5; The total mass percentage of all secondary crystalline phases in the transparent nepheline glass-ceramics is L, 0%<L≤5%; The average grain size of the transparent nepheline glass-ceramics is 20-60nm; The transparent nepheline glass-ceramics has a crystallinity of 20%-70%.

2. The transparent nepheline glass-ceramics according to claim 1, characterized in that: In terms of mole percentage, the transparent nepheline glass-ceramics comprises: 42.0-53.0% SiO2, 16.5-21.0% Al2O3, 17.5-22.5% Na2O, 0-1.0% K2O, 4.0-9.0% Li2O, 2.0-5.0% B2O3, 1.2-4.5% ZrO2, 0-0.5% TiO2, 1.0-3.5% P2O5, 0-2.0% MgO, and 0.1-0.5% SnO2; The molar numbers of the components of the transparent nepheline glass-ceramics satisfy at least one of the following relationships: 1) 0.6≤(Al2O3 / Na2O)≤1.2; 2)23.0%≤(Na2O+Li2O+K2O)%≤30.50%; 3)2.0%≤(ZrO2+P2O5)%≤7.0%; 4)2.25≤(SiO2+Al2O3) / (Na2O+Li2O+K2O)≤2.

75.

3. The transparent nepheline glass-ceramics according to claim 2, characterized in that: The transparent nepheline glass-ceramics also includes rare earth element oxides. In the transparent nepheline glass-ceramics, the molar ratio of the rare earth element oxides is at least 0.10%, and the rare earth element oxide is one of Y2O3 and La2O3.

4. The transparent nepheline glass-ceramics according to claim 2, characterized in that: The transparent nepheline glass-ceramics also includes a clarifier. In the transparent nepheline glass-ceramics, the molar proportion of the clarifier is 0.1-0.50%, and the clarifier is at least one of NaCl, Sb2O3, As2O3, nitrate, and sulfate.

5. The transparent nepheline glass-ceramics according to claim 1, characterized in that: The transparent nepheline glass-ceramics has an elastic modulus of ≥75 Gpa, a shear modulus of ≥34 Gpa, and a Poisson's ratio between 0.15 and 0.

20.

6. A method for preparing the transparent nepheline glass-ceramics according to claim 2, characterized in that: The preparation method comprises the following steps: Mixing, melting, clarifying, molding and annealing the compound corresponding to the oxide according to claim 2 to obtain a base glass; The base glass is heated to 590°C-680°C at a heating rate of 1-15°C / min, and kept warm for 15-120 minutes to obtain the transparent nepheline glass-ceramics.

7. A method for preparing chemically strengthened glass-ceramics, characterized in that: The preparation method comprises the following steps: The transparent nepheline glass-ceramics prepared according to claim 6 is placed in LiNO3, NaNO3, KNO3 or a mixed molten salt of at least two of the three in a molten state at a temperature of 420°C-480°C and immersed for 2-10 hours to obtain the chemically strengthened glass-ceramics.

8. A chemically strengthened glass-ceramic, characterized in that: The chemically strengthened microcrystalline glass is prepared by the preparation method described in claim 7.

9. The chemically strengthened glass-ceramics according to claim 8, characterized in that: When the thickness of the chemically strengthened glass-ceramics is less than 0.70 mm, for light in the wavelength range of 400 nm to 780 nm, the transmittance Tr of the chemically strengthened glass-ceramics is ≥ 88%, the color control LAB value is 0.80≤|B|≤1.40, and Haze≤0.20%; The surface four-point bending strength of the chemically strengthened glass-ceramics is ≥600Mpa, and the extrusion strength is ≥15Kgf; Under the impact of 80-grit sandpaper and a 200g weight, the chemically strengthened microcrystalline glass can withstand a height of ≥150cm and an impact energy of ≥0.30 joules.

10. Application of the transparent nepheline glass-ceramics described in claim 1 or the chemically strengthened glass-ceramics described in claim 8 in screen protection cover materials for consumer electronic products and vehicle-mounted display devices.